Economics for healthcare managers - Lee, Robert H., 1948- (Health Administration Press ; Association of University Programs in Health Administration, 2019)
"Issues of diversity, equity, and inclusion are of utmost importance in today's medical schools, and the University of Michigan is at the forefront of effecting change in this key area of medical education. Drs. Michael Mulholland and Erika Newman and the Department of Surgery at the University of Michigan School of Medicine developed the Michigan Promise with the goal of achieving better results and assisting other schools of medicine to make progress in this area, as well. The Diversity Promise: Success in Academic Surgery and Medicine Through Diversity, Equity, and Inclusion discusses the structure and implementation of this innovative program--information that is easily transferrable to any department in a school of medicine"--Publisher's description.